(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
In this work, enzymatic hydrolysis by cellulase in a soluble and an immobilized form was studied to convert lignocellulosic oil palm empty fruit bunch (EFB) biomass into fermentable sugars as a feedstock for bioethanol production. The cellulase was covalently immobilized with activated and functionalized polyethylene glycol (PEG) via glutaraldehyde coupling method. As a whole, the immobilized cellulase displayed 50% higher efficiency over free cellulase, in reducing sugar recovery during hydrolysis reactions at pH of 4.8 and temperature of 50Â°C. From the kinetic study, it showed that Michaelis constant (Km) and limiting velocity (Vmax) of immobilized cellulase were 179.2 mg/ml and 33.5 mg/ml.min respectively, comparable with the value for free cellulose, 171.8 mg/ml and 34.5 mg/ml.min respectively. This result could be attributed to the effect of PEG on the binding cellulase to substrate desorb substrates, and enables free interaction of cellulase to hydrolyse cellulose maximally